Power vacuum tubes handbook - Whitaker, Jerry C. (Electronics handbook series., 2012)
"This handbook examines the underlying technologies of each type of power vacuum tube device commonly in use today. It offers a comprehensive look at the important area of high-frequency/high-power applications of microwave power devices, making it possible for general principles to be translated to specific applications. Supporting mathematics and extensive technical illustrations and schematic diagrams are included to clarify the material presented. This new edition will provide the reader with important updates on new vacuum tube technology, devices, applications, design methods, and modulation methods.What's New in the Second Edition?Reviews the latest in new vacuum tube technology - new devices and refinements of existing devices that extend power and frequency capabilities identifies new applications for commercial and scientific research examines new frontiers on materials science - directly impacting construction, reliability, and performance outlines new methods of power tube design - yielding more efficient, lasting tubes describes new modulation methods affecting power tube design and application, including digital technologies"--